Diseño de un banco de pruebas para partes electromecánicas de un automóvil para Cesvi Colombia (2017)
This project carried out the design of a Test Bench for Alternators, compressors and starters, of automobiles for the Company Cesvi Colombia, in order to be able to make a diagnosis of the Mechanisms. In the first instance priority was given to the variables and needs of the company, Conducting studies to identify possible solutions to the problem. With The information obtained and after knowing in detail the operation of the Mechanisms under study; Design alternatives were proposed in order to Choose the one best suited to the scenario raised with respect to Functionality, efficiency and requirements of the company. Using the mechanical design methodology was carried out the simulation of the Structure of the Test Bank, using the finite element method MEF With NX 9.0 software; Which led to the analysis of efforts and the Identification of variables that should be considered in the design, such as Materials, dimensions, anchors, control mechanisms, among others. Finally, the manuals and protocols of both The mechanisms to be tested, such as proper use and assembly arrangement, Maintenance and operating standards. As well as the manufacturing plans of the testing bench.